2006
DOI: 10.1016/j.ajo.2006.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Members of the Fusarium solani species complex that cause infections in both humans and plants are common in the environment

Abstract: Members of the Fusarium solani species complex (FSSC) are increasingly implicated as the causative agents of human mycoses, particularly in the expanding immunocompromised and immunosuppressed patient populations. Best known as ubiquitous plant pathogens and saprotrophs, the FSSC comprises over 45 phylogenetically distinct species distributed among three major clades. To identify which species are associated with human infections, we generated multilocus haplotypes based on four partial gene sequences from 471… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
196
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(211 citation statements)
references
References 8 publications
11
196
1
3
Order By: Relevance
“…1). The resulting phylogenetic relationships remained in agreement with previous studies (Du et al 2012;Kristensen et al 2005;Zhang et al 2006). The isolates of the same species were grouped together in the resulting MP tree, supporting their correct identification.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…1). The resulting phylogenetic relationships remained in agreement with previous studies (Du et al 2012;Kristensen et al 2005;Zhang et al 2006). The isolates of the same species were grouped together in the resulting MP tree, supporting their correct identification.…”
Section: Discussionsupporting
confidence: 87%
“…Values marked with the same letters were not significantly different from each other according to Tukey's post-hoc tests. The standard deviations are shown as the error bars analyses (Zhang et al 2006) have revealed the existence of over 45 species belonging to the FSSC that had previously been identified as F. solani due to these species' morphological similarities. A high level of diversity of the F. solani isolates was also detected in our study, supporting the idea that these isolates are members of the FSSC rather than a single species.…”
Section: Discussionmentioning
confidence: 99%
“…G. fujikuroi/F. solani is one of the most frequently isolated fungus from soil and plant debris, but it is also a host-specific pathogen of a number of agriculturally important plants, including pea, cucurbits, and sweet potato [28,49,50]. G. intricans/F.…”
Section: G Xylarioides Is Not Present In the Community Of Endophyticmentioning
confidence: 99%
“…6) and known as the causal agent of Fusarium dieback of avocado (Eskalen et al 2012;Kasson et al 2013). The AFC belongs to FSSC clade 3, which is composed of pathologically important species of both humans and plants (Aoki et al 2014;O'Donnell et al 2008;Zhang et al 2006). Strain A was always isolated from the discolored xylem and necrotic phloem of E. variegata before tree death.…”
Section: Discussionmentioning
confidence: 99%
“…AB2, inoculated with P2-f11 and P2-f22; A2, inoculated with P2-f11; Ct2, no inoculation Table 2. We used the sequence data of F. staphyleae and 30 FSSC strains reported by Costa et al (2016), Kasson et al (2013), O'Donnell et al (2008O'Donnell et al ( , 2015 and Zhang et al (2006), which were obtained from GenBank for multiple sequence alignment using CLUSTAL W and analysis by MEGA7 (Kumar et al 2016). The phylogenetic relationship was inferred by using the maximum likelihood method based on the Jukes-Cantor model (Jukes and Cantor 1969).…”
Section: Fungal Isolation and Identificationmentioning
confidence: 99%